Network analysis of beta gene (HBB) haplotypes related to Hb S (B6 Glu - Val) in Denizli, Turkiye - Ozturk, Onur (Journal of the Pakistan Medical Association, 2025)
Numerous haplotypes related to the haemoglobin S mutation have been diagnosed worldwide and in the Denizli region of Turkiye. These subgroup haplotypes include Benin, Arab-Indian, Senegal, Bantu, Algeria, Cameroon, Central African Republic, Saudi and various other varieties. The current study was planned to determine the formation periods and network linkage relationships of genetic variations linked to haemoglobin S in the Denizli area and other geographical regions. The haplotype data was processed using Network software to calculate possible links between haplotypes and their formation dates. The results uphold the possibility that the haemoglobin S mutation may have come to the area through migratory pathways. According to analysis, the Benin haplotype historically formed first, followed by the Senegal and Arab-Indian haplotypes. These findings indicate that the haemoglobin S mutation might have reached the Mediterranean area long before the Silk Route migrations = 2,000 years ago.